Compound histories : materials, governance, and production, 1760-1840 - Roberts, Lissa, 1954-; Werrett, Simon (Cultural dynamics of science ;, 2018)
A history of chemical developments and their impacts on technology and society in France, Great Britain, and other parts of Europe.